The New Brussels I Regime and Arbitration – Finding an Interface - Hietanen-Kunwald, Petra; Koulu, Riikka; Turunen, Santtu (LeXonomica, 2017)
As the revision process of Brussels I Regime has focused on the abolition of exequatur procedures, the interface between the Regulation and arbitration has been mostly a side note. Regardless of the fact that the systems of the Brussels I Regime and arbitration are two separate autonomous systems, overlapping issues arise. These interfaces have been discussed in the case-law of ECJ and later during the revision process. In the end, recitals elaborating the interface were added to the preamble of the Regulation, but no changes to the arbitration exclusion were introduced. The recital 12 aims to clarify how the arbitration exclusion adopted in the Regulation should be interpreted in the future. However, future case-law of ECJ is elemental to define the full meaning of the recitals.